Benefits of an Immunogenic Personalized Neoantigen Nanovaccine in Patients with High‐Risk Gastric/Gastroesophageal Junction Cancer. Issue 1 (9th November 2022) - Liu, Qin; Chu, Yanhong; Shao, Jie; Qian, Hanqing; Yang, Ju; Sha, Huizi; Cen, Lanqi; Tian, Manman; Xu, Qiuping; Chen, Fangjun; Yang, Yang; Wang, Weifeng; et al.
Abstract: Personalized neoantigen vaccines have shown strong immunogenicity in clinical trial, but still face various challenges in facilitating an efficient antitumor immune response. Here, a personalized neoantigen nanovaccine (PNVAC) platform for adjuvant cancer immunotherapy is generated. PNVAC triggers superior protective efficacy against tumor recurrence and promotes longer survival than free neoantigens, especially when combined with anti‐PD‐1 treatment in a murine tumor model. A phase I clinical trial (ChiCTR1800017319) is initiated to evaluate the safety, immunogenicity, and prophylactic effect of PNVAC on preventing tumor recurrence in patients with high‐risk gastric/gastroesophageal junction cancer after adjuvant chemotherapy of postsurgical resection. The one‐ and two‐year disease‐free survival rates are significantly higher than historical record. PNVAC induces both CD4 + and CD8 + T cell responses as well as antigen‐experienced memory T cell phenotype. Furthermore, the immune response is persistent and remains evident one year after the vaccination. This work provides a safe and feasible strategy for developing neoantigen vaccines to delay gastric cancer recurrence after surgery. Abstract : Personalized neoantigen vaccine can trigger specific anti‐tumor T cell responses. However, there are some concerns with the use of neoantigen vaccine, including unfavorable pharmacokinetic profile and poor antigen presentation. A universal nanovaccine platform is built to overcome the above challenges and it demonstrates superior protective efficacy against advanced gastric cancer recurrence in preclinical studies and a phase I clinical trial.